Comparative Study on Solar Collectorâs Configuration for an Ejector-Refrigeration Cycle - Senjaya, Raffles; Astina, I Made (Journal of Engineering and Technological Sciences, 2008)
Solar collectorâs configuration plays important roleÂ  on solar-powered refrigeration systemsÂ  to work as heat source for generator . Three types of solar collector consistingÂ  of flat plate, evacuated tube, and compound parabolic solar collectorsÂ  areÂ  comparedÂ  toÂ  investigateÂ  theirÂ  performances.Â  TheÂ  performances consist of the behavior of heat which can be absorbed by the collectors, heat loss fromÂ  theÂ  collectorsÂ  and outlet temperature of working fluid at several slopes of theÂ  solarÂ  collectors.Â  TheÂ  newÂ  accurateÂ  analysisÂ  methodÂ  ofÂ  heatÂ  transferÂ  is conductedÂ  toÂ  predictÂ  theÂ  performanceÂ  ofÂ  theÂ  solarÂ  collectors.Â  TheÂ  analysisÂ  is basedÂ  onÂ  severalÂ  assumptions,Â  i.e.Â  skyÂ  conditionÂ  atÂ  BandungÂ  isÂ  clearÂ  andÂ  not raining from 08.00 until 17.00 and thermal resistance at cover and absorber plate isÂ  negligible. The numerical calculation results confirm that performance ofÂ  the evacuatedÂ  tubesÂ  solarÂ  collectorÂ  atÂ  theÂ  sameÂ  operatingÂ  conditionsÂ  is higherÂ  than theÂ  others.Â  ForÂ  theÂ  caseÂ  ofÂ  anÂ  evacuated-tubesÂ  solarÂ  collectorÂ  systemÂ  with aperture area of 3.5 m2, the maximum heat which can be absorbed is 3992Â  W for the highest solar intensityÂ  ofÂ  970 W/m2 at 12.00Â  withÂ  horizontal position ofÂ  the solarÂ  collector.Â  AtÂ  thisÂ  condition,Â  theÂ  highestÂ  outletÂ  temperatureÂ  ofÂ  waterÂ  is 347.15 K with mass flow rate 0.02 kg/s and inlet temperature 298 K.